Reliable simulation of timber structures by combined load and displacement control. Issue 3 (5th May 2015) - Gebhardt, Clemens; Kaliske, Michael
Abstract : Purpose: – The purpose of this paper is to propose a path-finding algorithm to solve problems with an arbitrary load-displacement relationship which results from geometrical and material nonlinear models to simulate e.g. timber structures realistically. Design/methodology/approach: – A method using combined load and displacement control for the Newton method along with path-characterising measures and sub-incremention is introduced. A path-related stiffness measure is used to identify the situation when it is necessary to select the displacement control and chose the best degree of freedom as a parameter instead of the load factor. The nonlinearity index extracts information about the convergence behaviour during one incremental step. Together with the reduction of the load increments it avoids leaving the equilibrium path. Findings: – The method is discussed based on numerical examples with highly nonlinear behaviour. It is capable to solve systems with decreasing load capacity and snap-back effects. Originality/value: – The algorithm combines load and displacement control and adaptively choses the method and the corresponding degree of freedom and cares for reliable path following.